2020
DOI: 10.5812/ijpbs.89168
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a Snoezelen Room on Fear, Anxiety, and Satisfaction of Nulliparous Women: A Randomized Controlled Trial

Abstract: Background: Pregnancy and childbirth are natural phenomena in a women’s life, associated with stress and anxiety, leading to adverse effects in the mother and fetus. Using complementary medicine, such as aromatherapy, music, light radiation, and aquariums in an environment that engage a person’s multiple senses can make mothers relax through mental deviations. Objectives: The aim of this study was to evaluate the effects of a Snoezelen room on fear, anxiety, and satisfaction of childbirth’s nulliparous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 53 publications
1
1
0
Order By: Relevance
“…They concluded that the study corroborated other studies that had shown that multi‐sensory rooms provided fear and pain amelioration, as impacted by endorphin production (relaxation) 32 . In another recent study, findings showed that fear, anxiety and satisfaction were impacted positively and significantly by labor and birth in Snoezelen Rooms 33 …”
Section: Further Review Of Studies: Impact Of Color and Light On Birthsupporting
confidence: 81%
See 1 more Smart Citation
“…They concluded that the study corroborated other studies that had shown that multi‐sensory rooms provided fear and pain amelioration, as impacted by endorphin production (relaxation) 32 . In another recent study, findings showed that fear, anxiety and satisfaction were impacted positively and significantly by labor and birth in Snoezelen Rooms 33 …”
Section: Further Review Of Studies: Impact Of Color and Light On Birthsupporting
confidence: 81%
“…32 In another recent study, findings showed that fear, anxiety and satisfaction were impacted positively and significantly by labor and birth in Snoezelen Rooms. 33 It is clear that fear amelioration is a significant aspect of birth environment design, related to creating calming and distracting spatial settings. In these studies, color and light have been shown to be quite effective in entry spaces as well as labor room settings in ameliorating fear and anxiety.…”
Section: Amelioration Of Fear and Stressmentioning
confidence: 99%